Evaluation of the Implementation of Tax Obligations of P2P Lending Providers - Pratiwi, Ratna Ika; Nuryanah, Siti (Graduate Program Magister Manajemen Pendidikan, 2024)
Peer-to-Peer (P2P) lending is a form of lending in which individuals or businesses borrow and lend money without involving traditional financial institutions as intermediaries. P2P lending operators have the additional administrative burden to withhold and reporting lender's interest in the Periodic Income Tax Return 23/26. The aim of research to analyze how the tax obligations of P2P Lending operators are implemented based on the six principles of ease of administration and four maxims uses a qualitative method with a case study approach at the Indonesian Joint Funding Fintech Association (AFPI). The results of this research show that the implementation of Withholing tax on interest has fulfilled the principles of certainty, simplicity, convenience, efficiency and equality, however there are still notes of things that need to be improved from a regulatory perspective by the DJP and from an administrative perspective by P2P lending operator.